2018
DOI: 10.1097/wnr.0000000000001128
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum stress transducer old astrocyte specifically induced substance positively regulates glial scar formation in spinal cord injury

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Most of them show a tissue-specific preferential expression, however, CREB3, CREB3L1, and CREB3L2 co-express in different cells of the CNS (Figure 2) where they participate in essential processes (Table 1 and Figure 3). For example, CREB3L1 and CREB3L2 are involved in neurite outgrowth (Macgillavry et al, 2011; Okuda et al, 2014) while CREB3 and CREB3L1 modulate (directly or indirectly) axonal growth after an injury (Ying et al, 2014; Sumida et al, 2018). CREB3 regulates pathogenic mechanisms of herpes and polio virus (Lu and Misra, 2000; Liang et al, 2006), and in non-CNS cells a CREB3-ARF4 signaling pathway mediates the susceptibility to pathogens (Reiling et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them show a tissue-specific preferential expression, however, CREB3, CREB3L1, and CREB3L2 co-express in different cells of the CNS (Figure 2) where they participate in essential processes (Table 1 and Figure 3). For example, CREB3L1 and CREB3L2 are involved in neurite outgrowth (Macgillavry et al, 2011; Okuda et al, 2014) while CREB3 and CREB3L1 modulate (directly or indirectly) axonal growth after an injury (Ying et al, 2014; Sumida et al, 2018). CREB3 regulates pathogenic mechanisms of herpes and polio virus (Lu and Misra, 2000; Liang et al, 2006), and in non-CNS cells a CREB3-ARF4 signaling pathway mediates the susceptibility to pathogens (Reiling et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Up-Regulation of its expression was also demonstrated in reactive astrocytes proximal to a spinal cord injury (Nikaido et al, 2002). Studies performed in CREB3L1 knock-out mice indicated that, in astrocytes, CREB3L1 promotes glial scars formation, impedes axon growth and functional recovery after spinal injury (Sumida et al, 2018). Furthermore, CREB3L1 protein expression was detected in astrocytes and in neuronal primary cultures obtained from hippocampi of mice, but its mRNA up-regulation was detected only in astrocytes after treatment with kainic acid (KA).…”
Section: Creb3 Family In the Central Nervous Systemmentioning
confidence: 99%
“…CREB3 factors have been characterized as regulators of genes-encoding components of the secretory pathway ( Fox et al, 2010 ; Sampieri et al, 2019 ). In addition, CREB3, CREB3L1, and CREB3L2 are expressed in different cell types of the CNS ( MacGillavry et al, 2011 ; Okuda et al, 2014 ; Ying et al, 2014 ; Sumida et al, 2018 ). We hypothesize that levels of the CREB3 family members could be modified during PC12 cell differentiation, and, therefore, mRNA levels of all were quantified by qRT-PCR assays ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in CREB3 agree with those observed in a microarray study performed on PC12 cells treated with NGF ( Dijkmans et al, 2008 ). Although it has been described that CREB3 participates in axonal regeneration ( Ying et al, 2014 , 2015 ) and that, in astrocytes, CREB3L1 impedes axon growth and functional recovery after spinal injury ( Sumida et al, 2018 ), many questions about the molecular mechanisms of CREB3 transcription factors in these neuronal processes remain unknown. In terms of the participation of CREB3 transcription factors in differentiation processes, our research group ( Garcia et al, 2017 ) has previously reported the adaptation of the Golgi complex in a CREB3L1-dependent manner in rat thyroid cells incubated with TSH (thyroid stimulating hormone).…”
Section: Discussionmentioning
confidence: 99%
“…OASIS is upregulated in reactive astrocytes after neuronal degeneration induced by kainic acid [ 26 ]. OASIS expression increases in reactive astrocytes after spinal cord injury, inhibiting neural regrowth, while knockdown promotes regrowth [ 27 , 28 ]. Developmental effects in Oasis-null mice include larger numbers of neural precursor cells (NPCs) and fewer GFAP-expressing astrocytes [ 26 ].…”
Section: Four Arg-tfs and Their Homologsmentioning
confidence: 99%